Kesehatan sebagai Hak Asasi: Perspektif Filosofis tentang Hukum Kesehatan - Maulana, Muhammad Asrul; Avrillina, Java Putri (Indonesian Journal Publisher, 2024)
The benefits of this research include improving health policies and laws that are more in line with Pancasila values and community needs. This research can also provide a better understanding of the right to health as a human right and contribute to stronger health advocacy. Thus, research on health as a human right from a philosophical perspective in health law has important relevance in ensuring the fulfillment of the right to fair, equitable and quality health for all Indonesian citizens. This research uses a multidisciplinary approach that integrates normative juridical law, specifically using a legislative approach and a philosophical perspective. Health development is a top priority with a focus on increasing health system resilience, response to crisis situations, and policies that are responsive to community needs. Thus, the implementation of the Pancasila Philosophy in the Health Law involves values such as mutual cooperation, social justice, balance, divinity and independence, which aim to realize health services that are inclusive, fair and in line with the needs of the Indonesian people.